PENGARUH UMUR PERUSAHAAN, UKURAN PERUSAHAAN, RETURN ON ASSETS DAN FINANCIAL LEVERAGE PADA UNDERPRICING PENAWARAN UMUM PERDANA - Saputra, Anom Cahaya; Suaryana, I G. N. (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study is an empirical study to test the effect of variable age of the firm, company size, return on assets and financial leverage to underpricing of initial public offering on the Indonesian Stock Exchange with the observation period 2010-2013. The samples using purposive sampling technique through certain criteria in order to obtain a sample of 57 companies observations. The analysis technique used in this research is multiple linear regression and hypothesis testing using t-statistic to test the partial regression coefficient and f-statistic to test the feasibility of the research model with a level of significance of 5%. It also made the classic assumption test including normality test, multicollinearity, heteroscedasticity test and autocorrelation test. The analysis showed that the age of the company no effect on underpricing, while the size of the company and the return on assets negative effect on underpricing, and financial leverage positive effect on underpricing.
Keywords: Underpricing, Age Company, Company Size, Return on Assets, Financial Leverage